2017
DOI: 10.1063/1.4978708
|View full text |Cite
|
Sign up to set email alerts
|

Multistate, multichannel coupled diabatic state representations of adiabatic states coupled by conical intersections. CH2OH photodissociation

Abstract: A coupled diabatic state representation, H, of the 1, 2, 3 A states of CHOH suitable for the description of the three channel, three state photodissociation process CHOH(1 A) + hv → CHOH(2, 3 A) → CHO(X, A) + H, cis-CHOH + H, trans-CHOH + H, is reported. The representation is based on electronic structure data (energies, energy gradients, and derivative couplings) obtained exclusively from multireference configuration interaction single and double excitation wave functions. Diabat shifting is employed to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…207 These findings have been rationalised by assuming initial excitation to both the 3 2 A (3p) and 2 2 A (3s) Rydberg states, the former of which can decay by passage through successive conical intersections in the RC-H stretch coordinate en route to both cis-and trans-HCOH products in their respective ground states. 208 The corresponding 3sn absorption of the 1-hydroxyethyl (CH3CHOH) radical extends to  > 500 nm. As with the CH2OH radical, studies involving selectively deuterated precursors and long excitation wavelengths identify O-H bond fission (leading to fast H atoms with an anisotropic recoil velocity distribution along with CH3CHO co-products) as the exclusive fragmentation channel, and theory 209 has again identified a conical intersection between the 2 2 A ( 2 n(3s/*)) and 1 2 A (ground state) PESs in the RO-H stretch coordinate that successfully explains this observation.…”
Section: Substituted Alkyl (And Related) Radicalsmentioning
confidence: 99%
“…207 These findings have been rationalised by assuming initial excitation to both the 3 2 A (3p) and 2 2 A (3s) Rydberg states, the former of which can decay by passage through successive conical intersections in the RC-H stretch coordinate en route to both cis-and trans-HCOH products in their respective ground states. 208 The corresponding 3sn absorption of the 1-hydroxyethyl (CH3CHOH) radical extends to  > 500 nm. As with the CH2OH radical, studies involving selectively deuterated precursors and long excitation wavelengths identify O-H bond fission (leading to fast H atoms with an anisotropic recoil velocity distribution along with CH3CHO co-products) as the exclusive fragmentation channel, and theory 209 has again identified a conical intersection between the 2 2 A ( 2 n(3s/*)) and 1 2 A (ground state) PESs in the RO-H stretch coordinate that successfully explains this observation.…”
Section: Substituted Alkyl (And Related) Radicalsmentioning
confidence: 99%
“…In a previous theoretical simulation of the unimolecular reaction, only the D 0 PES was used, and the GP effect and DBOC were ignored. We undertook a quantum dynamical study of the unimolecular reaction using a reduced-dimensional model including the O–H ( R ) and C–O bonds, the C–O–H angle, and the H–C–O–H torsional angle (ϕ), on the ab initio based diabatic PEM. , Interestingly, the overtone lifetimes immediately above the dissociation limit were found to be insensitive to the incorporation of the GP. A detailed analysis revealed that the tunneling paths through the equivalent saddle points on each side of the CI repel each other (see Figure ), due to the repulsive topography of the PES along ϕ.…”
Section: Nonadiabatic Tunnelingmentioning
confidence: 99%
“…We undertook a quantum dynamical study 70 71 on the ab initio based diabatic PEM. 72,73 Interestingly, the overtone lifetimes immediately above the dissociation limit were found to be insensitive to the incorporation of the GP. A detailed analysis revealed that the tunneling paths through the equivalent saddle points on each side of the CI repel each other (see Figure 5), due to the repulsive topography of the PES along ϕ.…”
Section: Dissociation: Constructive and Destructive Interferencesmentioning
confidence: 99%
“…In this work, we use a full 9D model to study the absorption spectrum of CH 2 OH (3p x ) based on the three-state diabatic PEM constructed by Malbon and Yarkony . The nuclear Hamiltonian of the system in the diabatic representation is given as follows: in which Η d,(3) is the 3 × 3 diabatic PEM.…”
Section: Theorymentioning
confidence: 99%